The relationship between greenspace and personal exposure to PM2.5 during walking trips in Delhi, India. (15th July 2022) - Mueller, William; Wilkinson, Paul; Milner, James; Loh, Miranda; Vardoulakis, Sotiris; Petard, Zoë; Cherrie, Mark; Puttaswamy, Naveen; Balakrishnan, Kalpana; Arvind, D.K.
Abstract: The presence of urban greenspace may lead to reduced personal exposure to air pollution via several mechanisms, for example, increased dispersion of airborne particulates; however, there is a lack of real-time evidence across different urban contexts. Study participants were 79 adolescents with asthma who lived in Delhi, India and were recruited to the Delhi Air Pollution and Health Effects (DAPHNE) study. Participants were monitored continuously for exposure to PM2.5 (particulate matter with an aerodynamic diameter of less than 2.5 μm) for 48 h. We isolated normal day-to-day walking journeys (n = 199) from the personal monitoring dataset and assessed the relationship between greenspace and personal PM2.5 using different spatial scales of the mean Normalised Difference Vegetation Index (NDVI), mean tree cover (TC), and proportion of surrounding green land use (GLU) and parks or forests (PF). The journeys had a mean duration of 12.7 (range 5, 53) min and mean PM2.5 personal exposure of 133.9 (standard deviation = 114.8) μg/m 3 . The within-trip analysis showed weak inverse associations between greenspace markers and PM2.5 concentrations only in the spring/summer/monsoon season, with statistically significant associations for TC at the 25 and 50 m buffers in adjusted models. Between-trip analysis also indicated inverse associations for NDVI and TC, but suggested positive associations for GLU and PF in the spring/summer/monsoon season; no overall patterns of association were evident in the autumn/winter season. Associations between greenspace and personal PM2.5 during walking trips in Delhi varied across metrics, spatial scales, and season, but were most consistent for TC. These mixed findings may partly relate to journeys being dominated by walking along roads and small effects on PM2.5 of small pockets of greenspace. Larger areas of greenspace may, however, give rise to observable spatial effects on PM2.5, which vary by season. Graphical abstract: Image 1 Highlights: Personal PM2.5 exposure in Delhi was much higher in the autumn/winter season. Lower PM2.5 exposure was related to NDVI and tree cover in spring/summer/monsoon. PM2.5 exposure was not associated with green land use during walking journeys. Higher PM2.5 exposure was linked to journeys with more overall green land use.